A Comparative Multimodal Study of Selected Cover Pages of the Newswatch Times and The Tell Magazines (British Journal of Multidisciplinary and Advanced Studies, 2023)
This research explores on a comparative multimodal explication of selected cover pages of two Nigerian news magazines - The Newswatch Times Magazine and The TELL Magazine. Three cover pages each were selected from the two magazines and analysed via Norgaard’s (2010) multimodal stylistics tool-kit. The study investigates how multimodal resources such as; colours, images, graphics and other para-linguistic elements displayed on the selected cover pages explore on meaning possibilities. The result reveals that both magazines applied rich multimodal resources on the selected cover pages to portray meaning-making on the aspects of economy, security, politics and public administration in Nigeria. Visually or symbolically speaking, both magazines either criticise or favour the present government in one way or another regarding polices related to economy, security, politics and other aspects of human endeavours via the use multimodal devices.